FORMING SPEAKING COMPETENCE FOR A1 ANDA2 LEVEL PUPILS - Qo’chqorova Zulfizar Abduxamidovna; Numonjonova Charosxon Nodirbekovna (Journal of Innovation in Education and Social Research, 2023)
This article highlights that improve A1 and A2 level students' speaking during the lesson, how they can improve speaking level and utilizing of cutting edge-technologies in not only teaching but also their general English.